Omega-3 supplementation in addition to prenatal vitamins during pregnancy is associated with lower rates of preterm birth and small for gestational age - Yakah, William; Haas, David M.; Grobman, William A.; Levine, Lisa D.; Reddy, Uma M.; Silver, Robert; Vacher, Claire-Marie; Wapner, Ronald J.; Penn, Anna A.; Firestein, Morgan R. (Frontiers in Nutrition, 2026)
Omega-3 fatty acids and prenatal vitamins support fetal growth, but most studies assess omega-3 supplementation without accounting for baseline prenatal vitamin use during pregnancy. In this secondary analysis, we obtained data from the large, prospective Nulliparous Mother-to-be (nuMoM2b) cohort study of 9,461 nulliparous individuals. Participants were enrolled through eight clinical sites across the United States. We compared adverse birth outcomes between those taking additional omega-3 supplements beyond standard prenatal vitamin intake (PNV-OM) vs. prenatal vitamins alone (PNV). PNV-OM intake was associated with significantly lower rates of preterm birth (5.04 vs. 8.41%, P < 0.001) and SGA (2.84 vs. 4.48%, P = 0.004). After adjustment for demographic and clinical differences, PNV-OM use remained associated with reduced odds of preterm birth (aOR 0.64, 95% CI: 0.47–0.86, P = 0.004) and SGA (aOR 0.64, 95% CI: 0.42–0.95, P = 0.03). However, given substantial socioeconomic differences between groups and the potential for residual confounding, these findings should be interpreted with caution. Supplemental omega-3 intake during pregnancy may provide an additive benefit beyond prenatal vitamins alone, but randomized trials are needed to determine whether this relationship is causal.